2018
DOI: 10.1111/zph.12520
|View full text |Cite
|
Sign up to set email alerts
|

High circulation of Hepatitis E virus in pigs and professionals exposed to pigs in Laos

Abstract: Epidemiological characteristics of hepatitis E Virus (HEV) differ due to the vast spatial heterogeneity in sanitation status, dietary habits and extent of exposure to animals. Although HEV infections are mostly asymptomatic, prognosis is poor for patients with compromised immune systems or pre-existing liver disease and during pregnancy. In developing countries, low hygienic standards and close human-animal interactions at farms and slaughterhouses likely favour zoonotic transmission of the virus. In this cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Our previous studies found high anti-HEV seroprevalence in Lao adults-approximately 41% (57/139) in those who had and 18% (38/210) in those who had no contact with swine. 16 Although HEV can be transmitted through blood transfusion, 30 31 we did not find any increase in seroprevalence in the transfused group, suggesting that transmission of HEV via blood transfusion is either not very efficient 32 or not very common in Lao PDR.…”
Section: Original Researchmentioning
confidence: 69%
See 1 more Smart Citation
“…Our previous studies found high anti-HEV seroprevalence in Lao adults-approximately 41% (57/139) in those who had and 18% (38/210) in those who had no contact with swine. 16 Although HEV can be transmitted through blood transfusion, 30 31 we did not find any increase in seroprevalence in the transfused group, suggesting that transmission of HEV via blood transfusion is either not very efficient 32 or not very common in Lao PDR.…”
Section: Original Researchmentioning
confidence: 69%
“…In our previous studies in Lao PDR, we found significant HEV exposure and people in close contact with swine or cattle had higher anti-HEV seroprevalence in comparison with the general population. 16 17 In contrast, parvovirus B19, which is mostly transmitted through respiratory secretions and normally has a mild clinical presentation in children, does not appear to be widespread in Lao PDR, although there are limited data. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Avian influenza virus Moderate poultry exposure (301-900 poultry-years) 21 Professional classification as a poultry seller 22 ≥10 years of occupational exposure 23 Another stall nearby, number of cages (more than five) 24 Workplaces near locations where H5N2 outbreaks in poultry were reported 25 Wholesale/retail live poultry markets 26 Female gender 22 23 Male gender 27 28 Coxiella burnetii Contact with small ruminants (sheep and goats) 29 Cattle contact at own or other farm 30 Keeping sheep or goats, exposure to arthropod bites 31 ≥3 daily goat-related tasks (milking, feeding, supply and removal, general animal healthcare and birth assistance), other goat breeds next to white dairy goat 32 Milking cattle, general healthcare of cattle, birth assistance, contact with raw milk, contact with cattle manure, contact with dead-born animals 33 Presence of cat(s) in goat stable, distance residence to nearest stable ≤10 m, distance to nearest positive farm 0-<4 km 28 Passed through the stores 34 Full working week, worked in cattle sector in the past 30 Age >50 years), rural area of residence, having little or no formal education 31 Lived as child on a ruminant farm, no farm boots for staff 32 Male gender 34 No respiratory protection mask 35 Living in rural areas 36 Hepatitis E virus Abattoir work, sewage work 37 Occupational contact with animals (forestry/pig farm workers) 38 Slaughterers 39 Exposure to soil, contact with swine 40 Having professions with exposure to pigs for more than 16.5 years 41 Unorganised swine farming 37 Woodcutting 42 Raw seafood processing 43 Feeding of pigs 44 Previous mission abroad (military forces) 45 Consumption of pork-liver sausages 37 Residence area 40 Age≥50 years, age group 25-34 years, ascending age, ages 40-49, 50-59, ≥60 and over 40 years 38 44 46-48 ≥7 working years ...…”
Section: Pathogen Disease Factor Workplace Factor Worker Factormentioning
confidence: 99%
“…A study in Hubei, China, identified elevated seroprevalence among rabbit slaughterhouse workers compared with community controls and observed a doseresponse relationship between increasing seroprevalence associated with duration of employment [48]. Khounvisith and colleagues evaluated HEV seroprevalence among commercial pig workers in Laos, a region with HEV endemicity among swine [49]. The authors observed 41% of workers were HEV seroprevalent, compared with 18% of controls, and workers exposed to piglets during the growth process were at elevated risk.…”
Section: Other Viral Infectionsmentioning
confidence: 99%